Characterization of artisanal gold mining activities in the tropics and their impact on sediment loading and stream flow in the Okame River catchment, Eastern Uganda - Barasa, Bernard; Kakembo, Vincent; Karl, Tiller (Environmental Earth Sciences, 2016)
Artisanal gold mining activities continue to degrade water resources in the tropical watersheds. In this study, we examined the spatial distribution of artisanal gold mining activities and their impact on sediment and mercury concentration in the Okame River catchment, Eastern Uganda. The spatial distributions of mining activities were assessed using both a TerraSAR-X radar satellite image of 2008 and Landsat image of 2013. Water samples and river bed deposits were collected on a monthly basis for a period of 1 year to assess the impact of mining activities on the streamflow variations and sediment concentration. Our results showed that the distribution of gold mining activities increased from 4.5 km2 in 2008 to 19.9 km2 in 2013. Human-induced sediment loading due to gold stone washing in the sampled tributaries of Okame River was responsible for the high concentration of suspended sediments (CSS), mercury and low water levels than prior to gold stone washing. River Omanyi (0.0191 mg l-1) was the most highly contaminated stream with mercury followed by Nankuke River (0.0163 mg l-1) and Nabewo River (0.0158 mg 1-1) in the Okame. There was also a significant concentration and trend of soluble mercury contamination from the sampled rivers (R2 = 0.8). The average concentration of mercury was found to be 0.004 ± 0.0009 mg l. This paper notes that artisanal mining activities have led to the reduction in streamflow rates, change of streamflow course and colonization of stream banks by riparian vegetation.
Keywords: Artisanal gold mining; Sediments; TerraSAR-X; Mercury; Streamflow